The “Season of the Witch” and the honest message - the role of mass mediain the stigmatization of the mentally ill - Dziwota, Ewelina; Porębska, Anna; Zadka, Łukasz; Olajossy, Marcin (Current Problems of Psychiatry, 2015)
Stigmatization of people who have been diagnosed as having a mental illness is a very common phenomenon in the contemporary world, and it means psychiatric patients are labeled, often throughout their lives. This stigmatization often comes about though negative portrayal of the afflicted, in the mass media. This action, in turn, shapes negative attitudes inside the greater society, and it evokes prejudices towards the mentally ill. The media is full of exaggerated negative images of psychiatric patients, showing them as people extremely dangerous and unpredictable. The article presents a review of the available literature concerning research conducted in Poland and in the world with respect to this phenomenon. The first part of the article is a presentation of the role of the mass media in the stigmatization of people with mental disorders. In it, examples are given of newspaper articles and television programs that employ pejorative and stigmatizing terms. As put forward in our work, these are often unreliable portraits of the mentally ill that are created by people who have had no direct contact with the patients. According to the theory of cultivation of attitudes, as well as general social learning theory (both mentioned by Stout), the media have a huge impact on the perception and treatment of psychiatric patients. The media is full of imprecise names of diseases, and the term "schizophrenia" is often used as a metaphor or for the needs of the context. People with mental illness are, therefore, one of the most stigmatized social groups inside the general population, and this phenomenon increases the marginalization of their social role. In the second part of the article, we try to show the mass media as being a potential tool for a change of attitudes from negative to positive among the general population, with respect to their attitudes towards the mentally ill. As discussed in the article, the sources of this stigma are deeply rooted in the culture and consciousness of the society at large. This positioning is understood as being dynamic and subject to the influences woven into the course of its development, with the influence of the mass media being one of the most conscious-building. This article highlights the need for supplying accurate information to the media, and the participation of psychiatrists and psychologists in creating programs dealing with problems of mental health.